Multidisciplinary residential treatment can improve perceptual‐motor function in obese children. (26th February 2015) - Gentier, Ilse; D'Hondt, Eva; Augustijn, Mireille; Tanghe, Ann; De Bourdeaudhuij, Ilse; Deforche, Benedicte; Lenoir, Matthieu
Abstract Aim This study evaluated the effects of a 10‐month multidisciplinary residential treatment programme on the perceptual‐motor function of obese children and compared them to children with a healthy weight. Methods We studied 26 obese Belgian children (10 girls and 16 boys) with a mean age of 10.1 years (±1.4 years), who followed a residential treatment programme consisting of moderate dietary restriction, psychological support and physical activity. The results were compared with 26 healthy weight children matched for age and gender. The anthropometrics and performance of both groups were assessed on two occasions, 10 months apart, based on simple and choice reaction time tasks and a tracking task using a stylus and tablet. Time by body mass index group interactions were investigated using repeated measure ANCOVAs, with age included as a covariate. Results No significant interaction effect occurred in either task. In contrast, the obese participants showed a significant improvement in tracking performance over time during the stylus and tablet tests, demonstrating mean deviation from the ideal curve. No difference in performance between baseline and follow‐up was observed in the healthy weight controls. Conclusion Taking part in a multidisciplinary residential treatment programme improved the perceptual‐motor function of obese children.